Sensitivity of air/mist non-equilibrium phase transition cooling to transient characteristics in a compressor of gas turbine. (July 2019) - Lin, Aqiang; Zheng, Qun; Jiang, Yuting; Lin, Xiang; Zhang, Hai
Highlights: Air/mist phase transition cooling with time-dependent is numerically simulated in a compressor. Fast Fourier transform is used to analyze the frequency attributions of fluctuating quantities. Effect of mist injection on flow field is discussed by the arithmetic-averaged result within one period. Relationship between transient characteristic and mist injection is investigated. Abstract: A comparative study of performance characteristics in a gas turbine compressor before and after water injection into the air is carried out to explore the relationships between the transient characteristic and mist injection. The Eulerian-Lagrangian particle tracking method is used for solving a process of phase transition cooling of water/air coupling, and the fast Fourier transform (FFT) is adopted to analyze the frequency attributions of fluctuating quantities with time-dependent including total pressure ratio, total temperature ratio, and efficiency. Results show, after mist injection into the compressor, droplet evaporation phase change leads to a higher characteristic fluctuation in the low-frequency region. The sensitivity of efficiency fluctuation is easily affected by the mist injection by comparing with the dry air condition. Within the mist conditions of 1–5 μm droplet sizes and 0.5–5% water/air ratios, the fluctuation of pressure in the compressor reaches a peak in small mist particle and low water/air ratio, resulting in a greater total pressure ratio. The temperature fluctuation gets the minimum in small droplet diameter and large water/air ratio, leading to a lower total temperature ratio. The fluctuation intensity of total pressure ratio, total temperature ratio and efficiency of compressor are increased to 3 times, reduced to 7/9 times and dropped to 3/5 times as water/air ratio increases from 0.5% to 5%, respectively; then, the fluctuation strength correspondingly increases 2 times, decreases 3/4 times and descends 6/7 times with the increase of droplet sizes from 1 μm to 9 μm. Thus, the fluctuation caused by low water/air ratio is higher than the small droplet diameter. Furthermore, efficiency fluctuation gets a minimum in small droplet size and appropriate water/air ratio.